Au-CuO core-shell nanoparticles design and development for the selective determination of Vitamin B6. (10th September 2015) - Kumar, Deivasigamani Ranjith; Manoj, Devaraj; Santhanalakshmi, Jayadevan; Shim, Jae-Jin
Graphical abstract: Highlights: Seed mediated growth of Au-CuO core-shell nanoparticle. Au-CuO core-shell nanoparticle provided good peak current for pyridoxine. Au-CuO/MWCNTs/GC exhibited excellent vitamin B6 peak separation with other vitamin. Abstract: This paper reports the synthesis of gold (core)-copper oxide (shell) nanoparticles using a simple seed mediated growth method. Pre-synthesized Au nanoparticles were used as seed materials for copper oxide shell growth, which were shown to be effective for Au-CuO core-shell formation. The novelty of this assembly strategy is that the exploitation of the Cu-ligand, which is thermolyzed on the Au nanoseed surface, results in the formation of CuO. Au-CuO core-shell nanoparticles were characterized by UV-visible spectroscopy, high resolution transmission electron microscopy (HRTEM) and X-ray photoelectron spectroscopy (XPS). The as prepared Au-CuO was used to fabricate a Au-CuO/MWCNTs/GC-modified electrode, which was applied to Vitamin B6 (pyridoxine) determination by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The MWCNTs enhance the pyridoxine oxidation rate by increasing the peak current with Au-CuO, hence pyridoxine oxidized lower operating potentials. The Au-CuO/MWCNTs/GC-modified electrode showed excellent electrochemical performance towards pyridoxine (PY) in the presence of other typical vitamins, such as riboflavin, ascorbic acid and uric acid. The linear calibration graph was obtained over the PY concentration range of 0.79 μM–18.4 μM and the detection limit (S/N = 3) was 0.15 μM. The Au-CuO/MWCNTs/GC-modified electrode showed good stability, repeatability and recovery of real sample analysis.